2005
DOI: 10.3402/ijch.v64i1.17954
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety about food supply in cree women with infants in Quebec

Abstract: Objectives. The objectives were to document the prevalence of maternal anxiety about food supply in Cree women who had 9-month-old infants, and to understand maternal and infant characteristics associated with anxiety. Study Design. The design was descriptive and combined both cross-sectional and retrospective analyses. Methods. The study took place in nine Cree communities in northern Quebec. Data on maternal characteristics in pregnancy (age, parity, anemia, smoking status) and infant characteristics (gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Household size can influence household food purchasing (31) , yet we found no association between household number and dietary variables. Approximately 20 % of Cree mothers in northern Québec worry about having enough money to buy food for their children (32) . Cree children, regardless of household size, may experience all or most aspects of food insecurity due to limited economic opportunities in the communities, the high cost of market food, and limited food choices (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Household size can influence household food purchasing (31) , yet we found no association between household number and dietary variables. Approximately 20 % of Cree mothers in northern Québec worry about having enough money to buy food for their children (32) . Cree children, regardless of household size, may experience all or most aspects of food insecurity due to limited economic opportunities in the communities, the high cost of market food, and limited food choices (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20 % of Cree mothers in northern Québec worry about having enough money to buy food for their children (32) . Cree children, regardless of household size, may experience all or most aspects of food insecurity due to limited economic opportunities in the communities, the high cost of market food, and limited food choices (32) . There is an inverse relationship between the energy density of food and its cost (33) .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of evidence that food insecurity is prevalent in Aboriginal communities, little information is known about the characteristics of the individuals or households experiencing this problem [13]. While numerous food system studies have been published on Inuit people living in the Canadian Arctic in recent years [7,14-23], there are still few food system studies with on-reserve FN communities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Affirmative responses to the question were considered by the authors to be evidence of anxiety about food supply. One-fifth of the participants in the study reported experiencing anxiety regarding their food supply (52). The Cree population in this rural northern Quebec community experience many of the same challenges in obtaining reasonably priced, nutritious foods that are experienced by Nunavut residents (53).…”
Section: Contaminants Diet and Nutritionmentioning
confidence: 99%